2015
DOI: 10.3109/14767058.2015.1026254
|View full text |Cite
|
Sign up to set email alerts
|

Sirenomelia: a review of embryogenic theories and discussion of the differences from caudal regression syndrome

Abstract: Even though the etiology of caudal regression syndrome (CRS) and sirenomelia remains unknown we tend to believe that sirenomelia and CRS might be different entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 33 publications
0
23
0
3
Order By: Relevance
“…Caudal dysgenesis is hypothesized to arise from a primary deficiency of caudal mesoderm (Duhamel, ; Alles and Sulik, ). This theory is supported by many authors (e.g., Duesterhoeft et al, ; Charlier et al, ; Thottungal et al, ; Gerard et al, ; Seidahmed et al, ; Moosa et al, ; Das et al, ; Lhuaire et al, ; Kaygusuz et al, ). Dias and Walker () suggested that a teratogenic event occurred during gastrulation that interfered with the formation of the notochord, resulting in abnormally developed caudal structures and concomitant neural tube defects.…”
Section: Sirenomelia and Its Overlap With Caudal Dysgenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Caudal dysgenesis is hypothesized to arise from a primary deficiency of caudal mesoderm (Duhamel, ; Alles and Sulik, ). This theory is supported by many authors (e.g., Duesterhoeft et al, ; Charlier et al, ; Thottungal et al, ; Gerard et al, ; Seidahmed et al, ; Moosa et al, ; Das et al, ; Lhuaire et al, ; Kaygusuz et al, ). Dias and Walker () suggested that a teratogenic event occurred during gastrulation that interfered with the formation of the notochord, resulting in abnormally developed caudal structures and concomitant neural tube defects.…”
Section: Sirenomelia and Its Overlap With Caudal Dysgenesismentioning
confidence: 99%
“…Due to lack of knowledge about the exact etiology and the clinical heterogeneity of sirenomelia regarding concomitant disorders, there are currently many hypotheses concerning its pathogenesis (reviewed by Valenzano et al, ; Garrido‐Allepuz et al, ; Arvind Athavale, ; Gabriele and Gianpaolo, ; Kaygusuz et al, ). Below, we will describe the most cited ones and try to give an overview of the many existing hypotheses.…”
Section: Overview Of Etiopathogenetic Mechanismsmentioning
confidence: 99%
“…Its prevalence has been reported to be 1/600,000-1,000,000 [ 2 ]. Although the mechanism underlying sirenomelia is still unknown, maternal diabetes mellitus, genetic predisposition, vascular hypoperfusion and exposure to teratogenic agents are among probable factors [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the gastrointestinal system anomalies described are rectal atresia, blind end colon, imperforate anus, esophagus atresia and omphalocele. Less commonly, pulmonary defects such as lung hypoplasia, diaphragmatic hernia and cardiac defects have been reported [ 3 - 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wax models showing sirenomelia from the "Luigi Cattaneo" Museum of Anatomical Waxes of the University of Bologna. Photo from Rossella Gelsi's private collection.accepted hypothesis postulates a primary vascular defect leaving the caudal part of the embryo hypoperfused(Isik et al 2015, Garrido-Allepuz et al 2011.…”
mentioning
confidence: 99%